Using general practitioners to recruit individuals with low socioeconomic position to preventive health checks is feasible: a cross sectional study - Nina Kamstrup-Larsen; Susanne Oksbjerg Dalton; Marie Broholm-Jørgensen; Lars Bruun Larsen; Janus Laust Thomsen; Christoffer Johansen; Janne Schurmann Tolstrup (Taylor & Francis Group, 2019)
Objective: To test whether demographic and health-related characteristics are associated with non-attendance of preventive health checks offered to individuals with low levels of education using proactive recruitment by the general practitioners. Design: A cross-sectional study. Setting: 32 general practice clinics in Copenhagen, Denmark. Subjects: A total of 549 individuals aged 45-64, with low levels of education, enrolled in the intervention group of a randomised controlled trial on preventive health checks offered by general practitioner. Main outcome measures: Non-attendance of the preventive health checks. Methods: (i) Descriptive characteristics of attendees and non-attendees and (ii) crude and adjusted multi-level logistic regression to examine associations of individual characteristics with non-attendance of preventive health checks. Results: Overall, 33% did not attend the prescheduled preventive health checks at their general practitioners. Non-attendees were more likely to live without a partner, be of non-Western origin, be daily smokers, have poor self-rated health, have higher pulmonary symptoms score, have increased level of stress, have low levels of self-efficacy, have metabolic risk factors or non-communicable diseases and have had no contact with their general practitioner within the past year. Conclusion: The findings suggest that, it is feasible to use general practitioners for recruiting individuals for preventive health checks. However, even in a trial targeting individuals with low levels of education, there are differences between attendees and non-attendees, with a more adverse health behaviour profile and worse health status observed among the non-attendees.KEY POINTS Current awareness • Non-attendance of preventive health checks offered to the general population is associated with low socioeconomic position and adverse health behaviours. Main statements • It is feasible to use general practitioners proactively in recruitment to preventive health checks offered to individuals with low socioeconomic positions. • In a trial targeting individuals with low levels of education, there were differences between attendees and non-attendees. • Non-attendance was associated with daily smoking, poor self-rated health, high stress and no contact with the general practitioner within the last year. Trial registration: ClinicalTrials.gov identifier: NCT01979107.